Optimalisasi Branding Produk dan Pengaplikasian Media Sosial sebagai Strategi Pengembangan pada UMKM di Kelurahan Rungkut Tengah Kota Surabaya - Dita Keysia Armelia Dwi Putri; Lia Nirawati (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Currently, businesses in Indonesia are dominated by MSME players. Micro, Small and Medium Enterprises (MSMEs) are one of the main pillars in driving the Indonesian economy. The current technological development is a good momentum in increasing the business development of MSMEs. The use of technology that is currently in demand by all circles is social media, in a business social media has a very important role in the development of a business. The business also cannot be separated from branding, because branding also plays an important role in creating a business identity. The existence of this progress requires MSMEs to adapt to existing challenges, the challenge in this era is how producers can sell or promote their various products in conventional ways and also digitalization. Competition that is quite tight in the current era of social media forces entrepreneurs to always develop their business. The purpose of this study is to implement the application of product branding and the use of social media for MSMEs in Rungkut Tengah Village during the KKNT. From this implementation, the author gets several final results, namely the creation of outputs such as the brand formed, logos, banners, packaging, google maps, and social media development.